Dialectical Behaviour Therapy dan Psikoedukasi Berbasis Kearifan Lokal Menurunkan Self-Harm Behaviour Pada Remaja: Study Quasy Eksperimen - Hayani, Mela; Rahmisyah, Rahmisyah; Saputra, Mahruri; Utama, Reka Julia; Riansyah, Ferdi; Putra, Eridha (Jurnal Ragam Pengabdian, 2026)
If adolescents are unable to cope with the changes that occur in themselves properly, then adolescents can take actions that are detrimental to themselves which are called self-harm behavior (SHB). SHB in adolescents can be treated by providing Dialectical Behavior Therapy (DBT) and psychoeducation based on local wisdom of Aceh. The purpose of this study was to determine the comparison of dialectical behavior therapy (DBT) and psychoeducation based on local wisdom on SHB in adolescents in Banda Aceh City. The study used a randomized control trial design method with a pretest-posttest two group design. The study will be conducted from February to August 2024. The population and sample were 68 adolescents divided into 2 groups, namely 34 people given DBT and 34 people given psychoeducation based on local wisdom. The measuring instrument used was the Self-harm Inventory (SHI) questionnaire. The analysis used univariate and bivariate with paired t-test and independent t-test. The results showed that there was a difference in SHB in adolescents before and after DBT (pvalue = 0.000; tcount 7.227). There was a difference in SHB in adolescents before and after local wisdom-based psychoeducation (pvalue = 0.000; tcount 10.240). The results of the study showed that there was no difference in SHB in adolescents between the DBT and local wisdom-based psychoeducation groups (p = 0.783> 0.05), meaning that both of these interventions were effective in reducing SHB in adolescents at SMA Kota Banda Aceh.